(untitled) (Proceedings of the International Conference on Education, 2023)
Cross-disciplinary courses in university engineering programmes provide supplemental knowledge that core technical subjects alone cannot provide. However, studies have shown that engineering students do not interact with such courses even when they appear complex, which affects educational success. Therefore, this study’s main objective is to determine the root causes of such limited levels of engagement, using fishbone diagrams (FBDs), fault tree analysis (FTA), and reliability block diagrams (RBDs) for data collection and analysis. Data was collected from a multidisciplinary cohort of mechanical, aerospace, and civil engineering students over a 5-year period. The top root causes were identified as "perception of engineering" and "nature of contents." The findings of this study were then used to create a revamped industry-inspired curriculum and multi-faceted assessment that is now currently deployed.